A new species of Bovista (Agaricales, Basidiomycota) from Khorchin sandland, China - Liu, Qianru; Bao, Haiying; Bau, Tolgor (Phytotaxa, 2025)
Bovista khorchinensis sp. nov., a new species of the genus Bovista Pers., this species is found in Khorchin sandland, Inner Mongolia. Maximum likelihood and Bayesian analyses were performed using a combined nuc rDNA internal transcribed spacer region (nrITS) and nuc 28S rDNA (nrLSU) dataset for the construction of phylogenetic tree. The species is characterized by basidiomata globose to subglobose, 12–22 mm in diameter. Exoperidium detaches at maturity and forms a persistent sandy cushion at the base. Endoperidium papery-leathery, ranges from black-red to signal brown, with a matte finish and a neatly edged apical pore at the top. Capillitium of Bovista-type with main stems up to 17 μm, pore is densely covered. Basidiospores globose to subglobose, Qm=1.07 (±0.04), finely verrucose, with a well-preserved pedicel 11–15 μm long. Morphological descriptions, line illustrations, and the ecological habits of the new species are provided in this study.